Nomination and Cognition: a New Typology of Linguistic Units Motivation - Selivanova, O. O. (Cognition, Communication, Discourse, 2018)
The article focuses on the new conception of motivation as a through linguo-cognitive process resulting in the formation of the onomasiological structure projected onto the structure of the knowledge about the designated. The author suggests new parameters for the typology of motivational relations, such as the status of a motivator in the knowledge structure, the rationality / irrationality and precedent-based character of the knowledge. The mechanisms and the varieties of propositional, associative-terminal, evaluative, and mixed motivation, as well as the nature of mythological and precedent-based motivation is described.